LIFE CYCLE ASSESSMENT OF METALLISED TEXTILES. THE CASE STUDY OF MATUROLIFE PROJECT - Wójcik-Augustyniak, Marzena; Szajczyk, Marek; Ojstršek, Alenka; Leber, Marjan (Management and Administration Journal, 2020)
This article provides an overview of the Life Cycle Assessment (LCA) method which supports manufacturers’ environmental information needs by evaluation of the environmental aspects and potential influences throughout the lifetime of the product. In the article results are presented of the first phase of the life cycle assessment of metallised textiles and the context for the analysis is a new project: „Metallisation of Textiles to make Urban living for Older people more Independent & Fashionable – MATUROLIFE”, implemented under the HORIZON 2020 Programme – “Advanced materials & innovative design for improved functionality & aesthetics in high added value consumer goods”.The article presents the most important assumptions for assessing the environmental effects associated with the metallization of various textiles, including primarily electroless copper coating, by calculating the demand for materials and energy, and taking into account emissions to air, water and soil, and by assessing their impact on the environment. The use of LCA as a management tool with great potential for making decisions within strategic business planning was analyzed.